When do R&D subsidies boost innovation? Revisiting the inverted U-shape - Juha Kilponen; Torsten Santavirta (Bank of Finland, 2007)
We show theoretically that a proportional R&D subsidy accelerates innovation activity at all degrees of competition in the modern Schumpeterian growth model, but less so at high degrees of competition. We then use company-level data on patenting activity, product market competition and R&D subsidies of Finnish firms during 1990 2001 to test the theoretical prediction. The empirical findings can be summarized as follows. Firstly, we find relatively strong evidence in favour of the inverted U-shape between competition and innovation. Secondly, we find some evidence that a direct R&D subsidy increases innovative activity at all but very high degrees of competition. This can be interpreted so mean that the R&D subsidy reinforces the Schumpeterian effect due to the negative cross-effect of R&D subsidy and competition. This is evident from the finding that an increase in the R&D subsidy steepens the inverted U relationship when competition is fierce.
URN:NBN:fi:bof-20140807676
Keywords: 330; competition; innovation; R&D subsidies; patents